PLASTIC WASTE POLLUTION AND ITS IMPLICATIONS FOR COASTAL MARINE ECOSYSTEMS (An Educational Study at SMPN 2 Semau) - Missa, Yudishinta; Boikh, Lebrina Ivantry; Ayubi, Aludin Al; Tampa, Ahazia Imanuel (Universitas Nusa Cendana, 2025)
Abstract - Waste management issues are a global problem that continue to have negative impacts on the environment. One factor contributing to the increasing amount of waste is the growing diversity of human activities. Coastal areas are highly vulnerable to waste pollution, particularly plastic waste. Plastic waste pollution in coastal marine areas is one of the fastest-growing environmental issues, causing significant negative impacts on marine ecosystems, including the destruction of marine habitats, disruption of the food chain, and the decline in coastal environmental quality. This problem is not only ecological in nature but also has social and economic impacts on coastal communities. This study aims to analyze the understanding and awareness of students at SMPN 2 Semau regarding plastic waste pollution and its implications for coastal marine ecosystems, as well as to examine the effectiveness of educational approaches in improving students’ knowledge and positive attitudes toward plastic waste management. The research method used is descriptive quantitative, with data collected through questionnaires, observations, and environmental outreach activities involving students as the main subjects. The results reveal that although most students already possess basic knowledge about the negative impacts of plastic waste on marine ecosystems, their awareness and involvement in waste management remain relatively low. Environmental education programs in schools can serve as one effective strategy to reduce plastic waste pollution in coastal areas, thus preserving marine ecosystems to support the sustainability of natural resources and the welfare of coastal communities. Keywords: Plastic waste, marine ecosystem, environmental education.